A Good Woman - Steel, Danielle (London Bantam Press, 2008)
Nineteen-year-old Annabelle Worthington was born into a life of privilege, raised amid the glamour of New York society, with glorious homes on Fifth Avenue and in Newport, Rhode Island. But everything changed on a cold April day in 1912, when the sinking of the Titanic shattered her family and her privileged world forever
Keywords: Upper class women -- Military nursing -- Rich people